2018
DOI: 10.3390/aerospace5030077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paper or Silver Nanowires-Loaded Paper Interleaves on the Electrical Conductivity and Interlaminar Fracture Toughness of Composites

Abstract: Abstract:The effect of plant-fiber paper or silver nanowires-loaded paper interleaves on the electrical conductivity and interlaminar fracture toughness of composites was studied. Highly conductive paper was prepared by surface-loaded silver nanowires. The percolation threshold appeared at about 0.4 g/m 2 . The surface resistivity reached 2.3 Ω/sq when the areal density of silver nanowires was 0.95 g/m 2 . After interleaving the conductive papers in the composite interlayers, in-plane electrical conductivity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…These results are hardly surprising as in the literature, many through‐thickness conductivity studies reported significant reduction of mechanical properties 36,53–61 (or did not report on mechanical properties 3,62–66 ).…”
Section: Resultsmentioning
confidence: 55%
“…These results are hardly surprising as in the literature, many through‐thickness conductivity studies reported significant reduction of mechanical properties 36,53–61 (or did not report on mechanical properties 3,62–66 ).…”
Section: Resultsmentioning
confidence: 55%
“…Work has been carried out that considers both the through-thickness conductivity and the interlaminar fracture toughness, with some work succeeding in maintaining or improving the interlaminar fracture toughness whilst also improving the conductivity [4,9,73]. The work of Guo and Yi [36] gives a novel approach, with the use of AgNW coated paper interleaves as a means of conductivity improvement. Most of the work done has used polymer or carbon based interleaves.…”
Section: Interleavingmentioning
confidence: 99%
“…The decrease in the conductivity due to the PEK-C interleave was partially mitigated with the AgNW coating of the PEK-C interleaves. The use of (AgNW) loaded paper interleaves by Guo and Yi [36] produced results showing improved through-thickness electrical conductivity, but also reduced mechanical performance due to poor interfacial bonding. The baseline composite consisted of UD carbon fibre fabric (UC3160 CCF 300, 3K) with epoxy resin (3226 AVIC Composites Tehnology Co., Ltd).…”
Section: Interleavingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong et al [7] performed cradle-to-gate life cycle assessment (LCA) study to demonstrate the possible advantages of ramie fibre on environmental impacts and to provide fundamental data for the further assessment of ramie fibre reinforced polymers (RFRP) and its structures. Guo et al [8] studied the effect of plant-fibre paper or silver nanowires-loaded paper interleaves on the electrical conductivity and interlaminar fracture toughness of composites. Experimental data show an increase in electrical conductivity and a decrease in interlaminar fracture toughness.…”
mentioning
confidence: 99%